Competency Corner, Part Three: Practice-based Weightings of the CBPS - Winslade, T.; Winslade, N; Chou, R; Cyr, B; Hawkins, B (Canadian Journal of Optometry, 2007)
The first two articles in this series outlined the task, research, terminology and processes the Competence Committee used to develop the Competency-based Performance Standards (CBPS). These standards were designed as a framework for revision of the Canadian Standard Assessment in Optometry (CSAO) to directly link the exam and practice requirements of Canadian Optometrists. This linkage required determination of the relative weight to be assigned to each of the various competencies. Working groups of practising optometrists rated the frequency and criticality of performance of each of the competencies using a standardized rating system. Results indicated that the majority of a revised CSAO would focus on providing comprehensive eye and vision care (78%), followed by management (11%) and collaboration (10%). The ratings also allowed calculation of the appropriate weighting of the underlying general attributes. The heaviest weighting was assigned to candidates’ professional optometric knowledge and the ability to apply this knowledge (41%), followed by communication (27%), planning (13%), ethics (11%) and self-directed learning (8%). The last article in this series will describe work to evaluate the competence-based weightings of the current CSAO and to describe plans for future versions of the CSAO.